Digital Horizons in Maritime Education: Navigating Challenges and Perspectives at STIP Jakarta - Marudut Bernadtua Simanjuntak (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
This research investigates the integration of digitalization challenges in maritime education, focusing on 240 cadets at the Maritime Institute Jakarta (STIP Jakarta). In their pivotal third semester, cadets undergo comprehensive preparation for internships, aligning with their majors—Nautical, Technical, and Port and Shipping Management. The study, adopting a qualitative descriptive approach, delves into cadets' perspectives on "An Integrative Approach for Digitalization Challenges of the Future Maritime Specialists" over three semesters. The findings reveal a nuanced landscape. While cadets acknowledge the importance of digital competencies, there is a notable gap in their confidence in preparedness. The positive correlation between perceived digital proficiency and overall professional competences signifies the integral connection between traditional maritime skills and digital literacy. Motivations driving cadets include enhanced employability (64%) and personal development (28%), pointing to a pragmatic and forward-looking mindset. The self-checked intelligence aspect exposes a potential gap between awareness and action, with 80% recognizing its importance but only 35% engaging in regular self-assessment. Perspectives on digital challenges reflect a balance between optimism (52%) and concerns about job displacement (38%), necessitating a holistic educational approach. The research underscores the paramount importance of English literacy, with 82% recognizing its significance in international maritime communication. The implications call for targeted curriculum enhancements, interventions promoting regular self-assessment, and a balanced approach to addressing digital challenges. Recommendations include bridging the gap between recognized importance and perceived preparedness, leveraging motivations for tailored programs, and cultivating a culture of self-reflection. In conclusion, this research provides a comprehensive understanding of cadets' perspectives, offering a roadmap for STIP Jakarta and similar institutions to navigate the digital horizons of maritime education effectively.